"I'm not batman" and other factors impacting bystander intervention against sexual violence in Australian nightlife settings. Issue 2 (6th May 2022) - Wrightson‐Hester, Aimee‐Rose; Allan, Alfred; Allan, Maria M.
Abstract: Unsolicited sexual behaviors that constitute sexual violence appear to be commonplace in nightlife settings in many countries and bystander intervention might be a way to eliminate them. However, few researchers have investigated the barriers and facilitators that affect Australian bystanders' likelihood to help, and these should be considered in the planning of bystander intervention programs. Using a grounded theory approach, we interviewed fourteen men and women about their perceptions of factors that might influence bystander behavior in Australian nightlife settings. The categories identified suggest that it is difficult for nightlife patrons to notice and identify sexual violence occurring around them. Further, nightlife patrons respect other patrons' right to engage in sexual behavior and will not intervene unless the recipient has been harmed by the behavior. Patrons are, also, much more likely to help when the recipient is a friend or a woman. Traditional bystander intervention programs on their own might not sufficiently address these barriers. Programs will also need to address patrons' perceptions of sexual violence and the prevailing social and gender norms in nightlife settings regarding sexual behavior.